From a word to the lexeme - Sadziński, Witold (Acta Universitatis Lodziensis. Folia Germanica, 2016)
In this article we find lexicographical reflections on the German (and Polish) dictionaries primarily in the context of the amount and structure of the contained therein lexemes. The author weaves considerations about the type of dictionary entries and how they can be lemmatised, eg. putting in dictionaries often only parts of compound words (eg. Affen-, Hunde-, -frei, -hungrig) to productively contribute to the development of vocabulary (eg. Affenschnell, Hundehitze, sozialversicherungsfrei, sexhungrig). The article also touched upon the issue of online dictionaries (digitized) and the increasingly important issue of foreign words, particularly English. The object of the considerations are mainly the Duden dictionaries, and also Wordbooks from Adelung, Klappenbach / Steinitz, Doroszewski, Zgółkowa, Żmigrodzki et al.